Different Extrapolation Methods in Problems of Forecasting - Стрелковська, Ірина Вікторівна; Стрелковська, І. В.; Стрелковская, Ирина Викторовна; Strelkovska, Iryna V.; Соловська, Ірина Миколаївна; Solovska, Iryna M.; Макоганюк, Анастасія Олегівна (Springer International Publishing, 2021)
The task of forecasting characteristics of self-similar trafﬁc in IoT network objects with a signiﬁcant number of pulsations and the property of long-term dependence is considered, which makes it difﬁcult to forecast in practice. Using the different extrapolation method of spline-extrapolation based on linear, cubic and B-cubic spline function and wavelet-extrapolation based on Haar-wavelet, the results of forecasting of self-similar trafﬁc are obtained. The comparison made allowed the results of trafﬁc forecasting based on the Haar-wavelet and the linear, cubic and B-cubic spline-function using wavelet- and spline-extrapolation. This will allow you to choose one or another extrapolationmethod to improve the accuracy of the forecast, while ensuring scalability and the ability to use it for various IoT applications to prevent network overloads.
Strelkovska I. V. Different Extrapolation Methods in Problems of Forecasting / I. V. Strelkovska, I. N. Solovska, A.O. Makoganiuk // Lecture Notes in Networks and Systems (LNNS,vol.152). - 2021. - P. 217-228. https://doi.org/10.1007/978-3-030-58359-0_12
Keywords: Self-similar trafﬁc; Internet of Things; Forecasting; Extrapolation; Spline-function; Wavelet-function; Research Subject Categories::TECHNOLOGY